Pengembangan Sumber Daya Manusia dan Motivasi Kerja terhadap Kinerja Perawat RS KIA PKU Muhammadiyah Kotagede - Hodiri Adi Putra; Debby Yulianthi Maria (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
Nurse performance is influenced by several factors, including human resource development (HRD) and work motivation. HRD development plays a strategic role in improving the quality of the workforce, including nurses. This development includes training, education, and skills development aimed at ensuring nurses have competencies that are in line with developments in health science and patient needs. The purpose of this study was to determine the effect of HRD development and motivation on nurse performance. The research method was quantitative with a cross-sectional approach. The sampling technique was total sampling, meaning that all 30 nurses were sampled. The analysis used univariate, bivariate using the t-test, and multivariate analysis using the F-test. The t-test results for the significant value of the HRD development variable were 0.000 <0.05, and work motivation was 0.519 >0.05. Simultaneously, the F-test obtained a significant value of 0.000 <0.05, so that all independent variables had a significant effect on the dependent variable together. Simultaneous testing showed the influence of human resource development and work motivation on nurse performance at the PKU Muhammadiyah Kotagede Special Hospital for Women and Children, Yogyakarta.).